Perjanjian Kerja Menurut Hukum Islam terhadap Harmonisasi dengan Undang-Undang Ketenagakerjaan di Indonesia - Siti Asyiah; Kharisma Febri Yanti; Ahmad Sihabbudin; Ramadhani Alfin Habibie (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze in depth the concept of employment agreements according to Islamic law and how these principles can be harmonized with the provisions of employment agreements in the Indonesian Manpower Law. This study aims to explore the basic values in Islamic law, such as justice, mutual consent, and prohibition of exploitation, which are the ethical basis for employment relations between employers and workers. On the other hand, this study also examines the provisions of positive law in force in Indonesia, especially after the enactment of the Job Creation Law, to see the extent to which these regulations reflect the principles of justice and protection of workers. In Islamic law, an employment agreement is viewed as an ijarah contract that has elements of agreement, willingness of both parties, and justice in the implementation of rights and obligations. Meanwhile, in Indonesian positive law, an employment agreement is the basis for employment relations between workers and employers which are regulated in writing or verbally with certain provisions. This study uses a library research method with a qualitative normative approach. The results of the study show that basically the principles of employment agreements in Islamic law do not conflict with the Manpower Law, and can even complement each other in terms of justice, protection of workers' rights, and voluntary agreements. Harmonization can be done through adjustments to sharia principles in the implementation of employment contracts and the need to strengthen moral and ethical aspects in employment relationships.